Does breast oncoplastic surgery improve quality of life? - Vieira, René Aloisio da Costa; Bailão-Junior, Antônio; de Oliveira-Junior, Idam (Frontiers in Oncology, 2023)
Breast Oncoplastic Surgery (OS) has established itself as a safe procedure associated with the treatment of breast cancer, but the term is broad, encompassing procedures associated with breast-conserving surgeries (BCS), conservative mastectomies and fat grafting. Surgeons believe that OS is associated with an increase in quality of life (QOL), but the diversity of QOL questionnaires and therapeutic modalities makes it difficult to assess from the patient's perspective. To answer this question, we performed a search for systematic reviews on QOL associated with different COM procedures, and in their absence, we selected case-control studies, discussing the main results. We observed that: (1) Patients undergoing BCS or breast reconstruction have improved QoL compared to those undergoing mastectomy; (2) In patients undergoing BCS, OS has not yet shown an improvement in QOL, a fact possibly influenced by patient selection bias; (3) In patients undergoing mastectomy with reconstruction, the QoL results are superior when the reconstruction is performed with autologous flaps and when the areola is preserved; (4) Prepectoral implants improves QOL in relation to subpectoral implant-based breast reconstruction; (5) ADM do not improves QOL; (6) In patients undergoing prophylactic mastectomy, satisfaction is high with the indication, but the patient must be informed about the potential complications associated with the procedure; (7) Satisfaction is high after performing fat grafting. It is observed that, in general, OS increases QOL, and when evaluating the procedures, any preservation or repair, or the use of autologous tissues, increases QOL, justifying OS.